Political terrain : Washington, D.C., from tidewater town to global metropolis - Abbott, Carl (University of North Carolina Press, 1999)
"In an explanation of the many identities Washington has taken on over time, Carl Abbott examines the ways in which the city's regional orientation and national symbolism have been interpreted by novelists and business boosters, architects and blues artists, map makers and politicians."--Cover